Assessing the role of primary healthy microglia and gap junction blocker in hindering Alzheimer’s disease neuroinflammatory type: Early approaches for therapeutic intervention - Anwar, Mai M.; Özkan, Esra; Shomalizadeh, Narges; Sapancı, Selin; Özler, Ceyda; Kesibi, Judy; Gürsoy-Özdemir, Yasemin (Frontiers in Neuroscience, 2023)
Alzheimer’s disease (AD) is a predominantly heterogeneous disease with a highly complex pathobiology. The presence of amyloid-beta (Aβ) depositions and the accumulation of hyperphosphorylated tau protein remain the characteristic hallmarks of AD. These hallmarks can be detected throughout the brain and other regions, including cerebrospinal fluid (CSF) and the spinal cord. Microglia cells, the brain-resident macrophage type of the brain, are implicated in maintaining healthy brain homeostasis. The localized administration of primary healthy microglia (PHM) is suggested to play a role in mitigating AD hallmark depositions and associated cognitive dysfunction. Carbenoxolone (CBX) is the most common gap junction blocker. It cannot effectively cross the blood–brain barrier (BBB) under systemic administration. Therefore, localized administration of CBX may be a recommended intervention against AD by acting as an antioxidant and anti-inflammatory agent. This study aims to determine whether the localized intracerebroventricular (ICV) administration of PHM and CBX may act as an effective therapeutic intervention for AD neuroinflammatory type. In addition, this study also aims to reveal whether detecting AD hallmarks in the spinal cord and CSF can be considered functional and effective during AD early diagnosis. Male albino rats were divided into four groups: control (group 1), lipopolysaccharide (LPS)-induced AD neuroinflammatory type (group 2), ICV injection of LPS + isolated PHM (group 3), and ICV injection of LPS + CBX (group 4). Morris water maze (MWM) was conducted to evaluate spatial working memory. The brain and spinal cord were isolated from each rat with the collection of CSF. Our findings demonstrate that the localized administration of PHM and CBX can act as promising therapeutic approaches against AD. Additionally, Aβ and tau toxic aggregates were detected in the spinal cord and the CSF of the induced AD model concomitant with the brain tissues. Overall, it is suggested that the ICV administration of PHM and CBX can restore normal brain functions and alleviate AD hallmark depositions. Detecting these depositions in the spinal cord and CSF may be considered in AD early diagnosis. As such, conducting clinical research is recommended to reveal the benefits of related therapeutic approaches compared with preclinical findings.